Hubungan Dukungan Orang Tua dengan Kedisiplinan Santri TPQ Surau Tengah Kelurahan Tanah Lapang Kota Sawahlunto - Andini, Dyta; Irmawita, Irmawita (Jurnal Family Education, 2025)
This research was motivated by the low level of discipline among students at the Surau Tengah TPQ, Tanah Lapang Village, Sawahlunto City. This study aims to (1) describe parental support, (2) describe student discipline, and (3) examine the relationship between parental support and discipline among students at the Surau Tengah TPQ, Tanah Lapang Village, Sawahlunto City. This study used a quantitative approach with a correlational approach. The population was 35 students at the Surau Tengah TPQ, Tanah Lapang Village, Sawahlunto City. The sample was taken using the Total Sampling method (Saturated Sampling). Data collection techniques used a questionnaire, and data analysis techniques were performed using the percentage formula and Product Moment. The results of the study found that: (1) The description of parental support at TPQ Surau Tengah, Tanah Lapang Village, Sawahlunto City is classified as low, this is proven by the results of the questionnaire data that has been conducted (2) The description of the discipline of students at TPQ Surau Tengah, Tanah Lapang Village, Sawahlunto City is categorized as low (3) There is a significant relationship between parental support and students at TPQ Surau Tengah, Tanah Lapang Village, Sawahlunto City.